Jual Beli Kiloan Baju Bayi Sistem Menurut Hukum Islam: Studi Kasus di Toko Rumah Katun Buaran Jakarta Timur - Hidayat, Yayat; Sugiarti, Alfira (Program Studi Hukum Ekonomi Syariah (Muamalah), 2024)
Buying and selling clothes using the kilo system is divided into several categories, one of which is the kilo decision category. Buaran Cotton House Shop East Jakarta Branch is one of the shops that implements this system. In the decision, the kilos of clothes sold are mixed up in shape, motif, and size so that customers do not know specifically which clothes are cheap and which are expensive, so there is an indication of an element of gharar. This research aims to describe the practice of buying and selling clothes using the kilo system and a review of Islamic law. The research method used is a qualitative approach with a case study method. The data collection techniques used were observations and interviews with employees and customers at the Rumah Katun Shop. The findings from this research are several problems, including a mix of brands, motifs, various forms of clothing between long and short, and customers not knowing specifically the prices of cheap and expensive clothes. The results of the findings of this research are the first to show that the practice of buying and selling clothes using the kilo system at the Rumah Cotton Shop East Jakarta branch has fulfilled the requirements for legal buying and selling, and the conditions for the goods being bought and sold are in accordance with Islamic law. Second, according to the ulama, ambiguity in the object of sale and purchase is identified as a type of gharar miqdar and is classified as light gharar which is permitted because it cannot be avoided and there is no element of compulsion and can be accepted by the buyer.